The Collapse of the Novel Genre and The Advent of Modernism in 20th Century European Literature - Nasiba, Normurodova (International Journal of Psychosocial Rehabilitation, 2020)
In this research paper explored the evolution of authors, their book and the subjects that they write about during, and after the world wars and the 20th century, including modernism, post modernism and post romance in Europe.